Diagnostic Accuracy of 16 Slice Contrast Enhanced CT Scan for Detection of Malignancy in Patients with Complex Adnexal Masses on Ultrasonography (Taking Histopathology as Gold Standard) - Sana Sharif; Asma Afzal Kiani; Nazia Mushtaq; Fareeha Khalid; Muhammad Uzair; Unaiza Sharif (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of a 16-slice contrast-enhanced CT scan (CECT) for the detection of malignancy in patients with complex adnexal masses on Ultrasonography (USG) (taking histopathology as the gold standard).